AVALIAÇÃO ESTÉTICA DE NOVE EDIFICAÇÕES PROJETADAS POR ARQUITETOS GANHADORES DO PREMIO PRITZKER DE ARQUITETURA - Reis, Antônio Tarcísio; Neumann, Júnia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this paper is to conduct an aesthetic evaluation of nine buildings designed by the Pritzker Architecture Prize winners from 1979 to 2013, and to identify the preferences and the reasons for the buildings more and less preferred by people with different levels and types of formal education. The means of data collection included online questionnaires accessible via the LimeSurvey software to three groups with different levels and type of formal education, in a total of 206 respondents. A total of nine images of buildings designed by architects winners of the Pritzker Prize were selected, evaluated individually and compared to each other in groups of three. Data analysis was performed using nonparametric statistical tests, such as Kendall's W and Kruskal-Wallis. The main results reveal, for example, a clear appreciation by any of the groups of the simultaneous presence of order and visual stimulus in the buildings, a greater appreciation of the idea of order by architects and a greater appreciation of the existence of visual stimuli by non architects.